Estrogen and soy isoflavonoids decrease sensitivity of medulloblastoma and central nervous system primitive neuroectodermal tumor cells to chemotherapeutic cytotoxicity - Scott M. Belcher; Caleb C. Burton; Clifford J. Cookman; Michelle Kirby; Gabriel L. Miranda; Fatima O. Saeed; Kathleen E. Wray (BMC, 2017)
Abstract Background Our previous studies demonstrated that growth and migration of medulloblastoma (MB), the most common malignant brain tumor in children, are stimulated by 17β-estradiol. The growth stimulating effects of estrogens are mediated through ERβ and insulin-like growth factor 1 signaling to inhibit caspase 3 activity and reduce tumor cell apoptosis. The objective of this study was to determine whether estrogens decreased sensitivity of MB cells to cytotoxic actions of chemotherapeutic drugs. Methods Using in vitro cell viability and clonogenic survival assays, concentration response analysis was used to determine whether the cytoprotective effects of estradiol protected human D283 Med MB cells from the cytotoxic actions of the MB chemotherapeutic drugs cisplatin, vincristine, or lomustine. Additional experiments were done to determine whether the ER antagonist fulvestrant or the selective ER modulator tamoxifen blocked the cytoprotective actions of estradiol. ER-selective agonists and antagonists were used to define receptor specificity, and the impacts of the soy-derived phytoestrogens genistein, daidzein, and s-equol on chemosensitivity were evaluated. Results In D283 Med cells the presence of 10 nM estradiol increased the IC50 for cisplatin-induced inhibition of viability 2-fold from ~5 μM to >10 μM. In clonogenic survival assays estradiol decreased the chemosensitivity of D283 Med cells exposed to cisplatin, lomustine and vincristine. The ERβ selective agonist DPN and low physiological concentrations of the soy-derived phytoestrogens genistein, daidzein, and s-equol also decreased sensitivity of D283 Med cells to cisplatin. The protective effects of estradiol were blocked by the antiestrogens 4-hydroxytamoxifen, fulvestrant (ICI 182,780) and the ERβ selective antagonist PPHTP. Whereas estradiol also decreased chemosensitivity of PFSK-1 cells, estradiol increased sensitivity of Daoy cell to cisplatin, suggesting that ERβ mediated effects may vary in different MB celltypes. Conclusions These findings demonstrate that E2 and environmental estrogens decrease sensitivity of MB to cytotoxic chemotherapeutics, and that ERβ selective and non-selective inhibition of estrogen receptor activity blocks these cytoprotective actions. These findings support the therapeutic potential of antiestrogen adjuvant therapies for MB, and findings that soy phytoestrogens also decrease sensitivity of MB cells to cytotoxic chemotherapeutics suggest that decreased exposure to environmental estrogens may benefit MB patient responses to chemotherapy.